A PEDAGOGICAL ANALYSIS OF DOK-BASED INSTRUCTION IN ENGLISH LANGUAGE TEACHING - Nazarova , Gulbakhor; Kuntugdiyeva , Inobatkhon (INTERNATIONAL CONFERENCE ON SCIENCE, INNOVATION AND GLOBAL DEVELOPMENT, 2026)
The Depth of Knowledge (DOK) framework’s pedagogical value and practical application in English language teaching (ELT) are examined in this article. DOK provides an organized method for encouraging deeper cognitive engagement, critical thinking, and communicative competence, whereas traditional instruction in EFL/ESL classrooms frequently emphasizes rote learning and surface-level knowledge. The study investigates how instructional tasks that support language development across reading, writing, speaking, and listening skills can be created using each of the four DOK levels. The article demonstrates how DOK-based instruction can promote higher-order thinking, improve linguistic proficiency, and support learning transfer in a variety of English language learning contexts through a pedagogical analysis of classroom activities, assessment strategies, and learner outcomes. The main point is that it’s important to put DOK ideas into lesson planning,